ANALYSIS OF POLICY AND DEVELOPMENT OF CEPI WATU BEACH TOURISM OBJECT AS A SUSTAINABLE TOURISM DESTINATION IN NANGA LABANG VILLAGE, BORONG DISTRICT, EAST MANGGARAI REGENCY - Saputra, Evabius (Universitas Dharmawangsa Medan, 2025)
This reserarch aims to analyze local government policies and formulate strategies for developing the Cepi Watu Beach Tourism Object as a sustainable tourism destination in Nanga Labang Village, Borong District, East Manggarai Regency. Cepi Watu Beach has stunning natural potential, a strategic location, and rich local culture. However, its management is considered less than optimal, especially related to the lack of facilities, inadequate infrastructure, and lack of local government support at the beginning of its development. This study uses qualitative methods with descriptive analysis and SWOT analysis (Strength, Weakness, Opportunity, Threat) to determine the strategic position and policy recommendations. The results of the SWOT analysis indicate that Cepi Watu Beach is in Quadrant I (Aggressive Strategy), which means this destination has great internal strength but faces significant external threats. The conclusion of the study shows that the development of Cepi Watu Beach requires support from the main components of tourism, namely: Attractions (natural beauty and panorama of Mount Poco Ndeki), Accessibility, and Amenities (supporting facilities such as toilets, gazebos, and parking areas). Recommended strategic policies include the development of community-based ecotourism supported by local governments, increased promotion through digital media, the construction of public facilities, and the establishment of formal management to ensure sustainability. Synergy between the district and village governments, as well as the active participation of local communities, is needed to overcome obstacles such as limited human resources and potential environmental degradation.